Novel 8-hydroxyquinoline derivatives targeting β-amyloid aggregation, metal chelation and oxidative stress against Alzheimer's disease. Issue 12 (23rd July 2018) - Yang, Xuelian; Cai, Pei; Liu, Qiaohong; Wu, Jiajia; Yin, Yong; Wang, Xiaobing; Kong, Lingyi
Graphical abstract: Highlights: Novel multi-target-directed ligands against Alzheimer's disease were designed. Profiles targeting A β -aggregation, metal chelation, oxidative stress and neuroprotection were tested. Compound 5b showed interesting pharmacological activities. Abstract: A series of multitargeted 8-hydroxyquinoline derivatives were designed and synthesized for the treatment of Alzheimer's disease (AD). In vitro studies indicated that most of the prepared compounds exhibited significant inhibitory effects against self-induced A β 1−42 aggregation and potential antioxidant properties especially compound 5b (IC50 = 5.64 μM for self-induced A β aggregation; the oxygen radical absorbance capacity using fluorescein (ORAC-FL) value is 2.63 Trolox equivalents). Notably, 5b can chelate biometals and inhibit Cu 2+ /Zn 2+ -induced A β 1−42 aggregation. The cell assays showed that 5b had excellent protective effects against oxidative toxin H2 O2 and presented low neurotoxicity in PC12 cells. Furthermore, 5b could penetrate the blood–brain barrier (BBB) in vitro and did not show any acute toxicity in mice at doses up to 2000 mg/kg in vivo . Our findings provide a rationale for the potential application of compound 5b as a lead compound in AD therapy.